2005
DOI: 10.1073/pnas.0507144102
|View full text |Cite|
|
Sign up to set email alerts
|

Sex and estrogenic effects on coexpression of mRNAs in single ventromedial hypothalamic neurons

Abstract: (102, 14446-14451; first published September 26, 2005; 10.1073͞pnas.0507144102), the authors note that ''%'' was added after several numbers, due to a printer's error. On page 14449, right column, the second sentence under Estrogen Treatment Increases Number of ER␣, ER␤, OTR, and PKCs in Female Rats, ''In estrogen-treated animals, these numbers were higher than in the oil group, ER␣ (66% vs. 20%), ER␤ (39% vs. 14%), OTR (56% vs. 15%), PKC␦ (28% vs. 8%), PKC (30% vs. 8%), and PKC (44% vs. 12%) (P Ͻ 0.05 in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 64 publications
(69 reference statements)
1
18
1
Order By: Relevance
“…The VMHvl and VMHdm are both targets for gonadal steroids, but differ in the proportion of cells expressing ER and AR mRNA (Simerly et al, 1990;Devidze, et al, 2005). Data from the current study suggest that VMHvl and VMHdm volume may underlie some of these sex differences in function, since they are sexually dimorphic in this regard.…”
Section: Sex Differencesmentioning
confidence: 59%
“…The VMHvl and VMHdm are both targets for gonadal steroids, but differ in the proportion of cells expressing ER and AR mRNA (Simerly et al, 1990;Devidze, et al, 2005). Data from the current study suggest that VMHvl and VMHdm volume may underlie some of these sex differences in function, since they are sexually dimorphic in this regard.…”
Section: Sex Differencesmentioning
confidence: 59%
“…In males, the VMH is critical in the regulation of sexual and aggressive behaviors primarily through the actions of estrogen on ER ␣ [Harding and McGinnis, 2004;Nelson and Trainor, 2007]. OT receptor expression in the VMH is up-regulated following increases in estradiol [Bale et al, 2001] or decreases in progesterone [Windle et al, 2006], and estrogen and oxytocin receptor mRNA is found to be co-expressed in VMH neurons [Devidze et al, 2005]. Taken together with our data, these findings suggest that variation in maternal care across the whole of the postnatal period can induce changes in offspring reproductive strategies.…”
Section: Neurobiological Changes Associated With Weaning Age: Plasticmentioning
confidence: 88%
“…Doing this, Devidze et al [36] found that the population of VMN neurons expressing ER-alpha was different from those expressing its likely gene duplication product ER-beta, and that an extremely high proportion of neurons expressing either ER also coexpresses mRNA for the oxytocin receptor. Patterns of triple coexpression among ERs, OTR, and each selected PKC isoform were signifi cantly different between female and male.…”
Section: Molecular Biology Of Estrogen Action In the Brainmentioning
confidence: 99%
“…A new way of studying estrogenic effects on gene expression in the brain is to use micropipettes to suck the mRNA contents from individual nerve cells to study the coexpression of genes in single neurons [36]. Doing this, Devidze et al [36] found that the population of VMN neurons expressing ER-alpha was different from those expressing its likely gene duplication product ER-beta, and that an extremely high proportion of neurons expressing either ER also coexpresses mRNA for the oxytocin receptor.…”
Section: Molecular Biology Of Estrogen Action In the Brainmentioning
confidence: 99%